Analisis Pemberian Wasiat Wajibah terhadap Ahli Waris Beda Agama Pasca Putusan Mahkamah Agung Nomor 331 K/Ag/2018 - Raharjo, Alip Pamungkas; Dwi Putri, Elok Fauzia (Jurnal Suara Hukum, 2019)
In Article 171 letter (c) Instruction of the President of the Republic of Indonesia Number 1 of 1991 concerning Compilation of Islamic Law affirms that the rights of non muslim heirs to the inheritance of Islamic heirs do not obtain inheritance from the inheritor's inheritance. However, in its development because it felt unfair, the Supreme Court through The Supreme Court Decision Number 368.K / AG / 1995 provided a way for joint cooperation of different inheritance through a wasiat wajibah. But in its development, this provision was changed again by a landmark decision from the Supreme Court, namely through the Decision of the Supreme Court Number 331 K / AG / 2018 because there was a change in the value of justice in the community. The research method used normative research with constitutional approach, conceptual approach and case approach. This study aims to explain the rights of non muslim heirs to the inheritance of Islamic heirs before and after the Decision of the Supreme Court Number 331 K / AG / 2018. The results showed that prior to the Supreme Court Decision Number 331 K / AG / 2018, heirs of non muslim religions were given a share of inheritance in the form of a wasiat wajibah for Â¾ of the inheritance inheritance. Post the Decision of the Supreme Court Number 331 K / AG / 2018, the amount of wasiat wajibah will change to Â¼ from the inheritor's inheritance.Â